Exploring the Characteristics of Physical Exercise in Students and the Path of Health Education - Peng, Xintong; Tang, Lijun (Frontiers in Psychology, 2021)
College students are taken as the research sample, with the purpose of exploring the characteristics of students’ physical exercise and health education path under artificial intelligence (AI) algorithm. Firstly, related literature is studied to understand the physical education system of college students. Then, the current situation of college students’ physical exercise is investigated through the interview survey, and the mathematical statistics method is used to analyze the survey results. Moreover, the necessity and paths to carry out health education are discussed through the analysis of college students’ physical exercise behavior. Finally, the college smart sports classroom is constructed using AI and the big data analysis method. The experimental results indicate that more than 50% of college students can actively participate in physical exercise. Besides, boys are more likely to take dangerous coping behaviors, while girls are more prone to choose resisting coping behaviors. In addition, there is little difference in age of the distribution of different coping behaviors in physical exercise. Freshmen are more inclined to take risky coping behaviors, and the quantity of students taking resistant coping behaviors increases with the increase of grade. Therefore, relevant physical health education for college students can promote the good habit of health exercise. This study can provide a reliable experimental basis for the development of sports education in the future.